Relevance of Indian traditional tisanes in the management of type 2 diabetes mellitus: A review - Devi Datt Joshi; Lokesh Deb; Bharat G. Somkuwar; Virendra Singh Rana (Elsevier, 2023)
Background: Tisanes are a potential source of phytochemicals to reduce disease risk conditions and are used to protect from non-communicable diseases, globally. A few tisanes have gained more popularity than others depending on their chemical composition based on the geographical origin of the used herb. Several Indian tisanes have been claimed to have traits beneficial to people with or at a high risk of type 2 diabetes mellitus. Under the concept, the literature was reviewed and compiled into a document to highlight the chemical uniqueness of popular Indian traditional tisanes to be more informative and potent as per modern medicine to overcome type 2 diabetes mellitus. Methods: An extensive literature survey was conducted using computerized database search engines, such as Google Scholar, PubMed, ScienceDirect, and EMBASE (Excerpta Medica database) for herbs that have been described for hyperglycemia, and involved reaction mechanism, in-vivo studies as well as clinical efficacies published since 2001 onwards using certain keywords. Compiled survey data used to make this review and all findings on Indian traditional antidiabetic tisanes are tabulated here. Results: Tisanes render oxidative stress, counter the damage by overexposure of free radicals to the body, affect enzymatic activities, enhance insulin secretion, etc. The active molecules of tisanes also act as anti-allergic, antibacterial, anti-inflammatory, antioxidant, antithrombotic, antiviral, antimutagenicity, anti-carcinogenicity, antiaging effects, etc. WHO also has a strategy to capitalize on the use of herbals to keep populations healthy through effective and affordable alternative means with robust quality assurance and strict adherence to the product specification.